Gene cloning, protein characterization and structural prediction of Amaranthus tricolor transketolase - Rajeendran, Allgendran (2013)
This study focused on gene cloning, protein characterization and structural prediction of Transketolase enzyme from Amaranthus tricolor. Oxidative Pentose Phosphate Pathway (OPPP) oxidative pentose phosphate pathway (OPPP) fulfills an essential role in metabolite intermediate of carbohydrate metabolism via the oxidation of glucose-6-phosphate in prokaryotic and eukaryotic cells. The non-oxidative branch of this pathway provides erythrose 4-phosphate for the shikimate pathway, the products of which are used for the synthesis of aromatic amino acids, flavonoids, and lignin, and ribose 5- phosphate for nucleic acid synthesis. Transketolase play important role in photosynthesis and glycolysis. Although the contribution of transketolase in plant system is important, study of this enzyme is still limited. There were only seven plants that TKT genes had been isolated so far, thus this leads to my first objective of my study is to isolate TKT gene from A. tricolor to compare its identity with other organisms. Unlike bacteria, fungal and all other animals, the pentose phosphate pathway is complete in the cytosol of these living system and all enzymes of this pathway localized in the cytosol. However, in plant system, the first phase of pentose phosphate pathway is complete in the cytosol of plant but sub-localization for non-oxidative pentose phosphate pathway is still remain unclear. The identification gene of TKT was done by RT-PCR with gene specific primer, followed by cloning, sequencing and gene expression. The present study had isolated 1963bp transketolase from A. tricolor. Similarity studies using ClustalW2 and phylogenetic studied found that A. tricolor TKT and Spinach sp. transketolase has 85% identity. This may be due to classification system both plants are in the same family, Amarathaceae. Analysis by Target P 1.1 and Chloro P revealed that the A. tricolor is localized in the chloroplast. The complete DNA sequence of the A. tricolor TKT gene was showed an open reading frame of 1943 nucleotides that encodes for 646 amino acid residues. A. tricolor TKT was expressed in E.coli BL21, using pET 32(b+) as a vector. The purified recombinant A. tricolor TKT protein size was determined by SDS-PAGE that give 70kDa. In addition, the 3D protein structure of A.tricolor transketolase was analysed by using PS2 and secondary its structure was predicted by Phyre2. As conclusion, A. tricolor transketolase was successfully isolated and subcellular-localization was found chloroplast in plant system. This led to conclusion that the OPPP is incomplete in the cytosol of A. tricolor. This study shows that A.tricolor transketolase has major functional role in the plastidic through the OPPP and could be an important required step for the production of secondary metabolites in plants.